PENGGUNAAN MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN BAHASA INGGRIS (STUDI KASUS DI SDN 3 TARUBASAN KLATEN) - Suryanti Galuh Pravitasari; Muhammad Lutfi Yulianto (Profesi Pendidikan Dasar, 2017)
This research aimed to find out whether the use of interactive multimedia in class contributes significant role in the success of the English teaching and learning process. The object of the study was the third grade students of SDN 3 Tarubasan, Klaten. This study is categorized as a class action research which was carried out in two cicles with five meetings each. It was done in the even semester of 2015/2016. A pre-test was given to the objects of the study to record their initial score before the use of the interactive multimedia was implemented. The mean of the pretest was 68,7 with only 3 Objects of the study meeting the passing grade score of 69. At the end of the first cycle, a post-test was given which resulted in a mean of 70,7. The number of the object of study meeting the passing grade score accelerated As much as 61,5%. Finally, after the second cycles was done, the mean of the post-test was 82,6 with all objects of the study met the passing grade score. It means that there is an increasing of 11,9 point  in the students’ achievement from the prior-to the treatment with interactive multimedia tool to the first cycle and 13,9 point from the first to the second cycle. All of the objects of the study have also successfully met the passing grade score. Therefore, it can be concluded that the use of interactive multimedia in the English teaching and learning process is proved to give significant influence to the students’ final achievement.